(3edNU cJGH ebGdI GdJGL aj UaGJ GdfHj Udi Gddg Ydjg hSdes - (3ehab GdOjf YHO GdWj Hf jhS GdHZOGOjs
(3ChdgG (B:s
[(3hHYO(B] (3gPG edNU (B[(3cPG(B] (3hGdeNJGQ ef cJGH GdJGL aj UaGJ GdfHj Ui Gddg Ydjg hSde s
(3BNQgG (B:s
(3hgPG BNQ eG CQOJ JdNjUg ef cJGH JYGdi (B[(3cPG(B] (3GdJGL s
(3Vef eLehY , JQJjHgG (B: (3ef U (B164 - (3U(B167s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs